Redesign Of BUMDes And MSMEs Marketplace Platform Using User Centered Design Method - Tirta Cahyatama, Muhammad Widya; Wardhana, Ariq Cahya (JURNAL RISET KOMPUTER (JURIKOM), 2025)
This research centers on the redesign of Waroeng Kita, a digital marketplace platform developed to facilitate transactions for Village-Owned Enterprises (BUMDes) and Micro, Small, and Medium Enterprises (MSMEs) in rural Indonesia. An initial usability assessment conducted for this study revealed a low System Usability Scale (SUS) score of 49.16, classifying the platform as "Not Acceptable" and highlighting significant usability challenges. To address these issues, the study systematically applied the User-Centered Design (UCD) methodology, following an iterative process aligned with the ISO 9241-210:2019 standard. Across two design iterations , critical usability flaws, including a static cart, unclear input forms, and unfamiliar terminology —were systematically resolved based on direct user feedback. The final evaluation after the second iteration demonstrated a substantial improvement, with the average SUS score increasing to 70. This score elevates the system to a "Marginally Acceptable" status (Grade C), confirming that the UCD approach is highly effective for enhancing system usability, particularly for users in rural settings with limited digital literacy. The study provides practical insights for creating more inclusive digital solutions in similar socio-economic contexts.